Der Lebenslauf als Quelle: Fallrekonstruktive Biographieforschung anhand personenbezogener Akten - Müller-Botsch Christine (Österreichische Zeitschrift für Geschichtswissenschaften, 2008)
This essay presents a method of biographical case reconstruction based on personal files and records of the NSDAP, including biographical documentation and autobiographical reports of the party’s low-level functionaries. Historical analysis is combined with a sociological biographical approach in order to reconstruct both a life history (experienced life) and a self-reported life story (presented life). This process of reconstruction is illustrated in the case of a low-level functionary of the Nazi Party, based on an analysis of NSDAP and denazification documents. Christine Müller-Botsch maps out the use of these sources for biographical, reconstructive approaches to historical research, and discusses the possibility of theoretical generalization based on case reconstructions.